Emergency Department Registered Nurses’ Perceptions of Substance Use Disorders and Supervised Consumption Sites / Perceptions du personnel infirmier autorisé des services d’urgence concernant les troubles liés à l’utilisation de substances et les sites de consommation supervisée - Ilievska, Aleksandra; Pittman, Gina; Ralph, Jody (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Background: Due to the increased drug-related harms that Canada is facing, a stronger emphasis has been placed on harm reduction strategies, such as supervised consumption sites (SCSs).There is a lack of literature on emergency department (ED) registered nurses’ (RNs’) perceptions of SCSs and substance use disorders (SUDs), especially in small- to mid-sized Canadian cities.Objective: This descriptive study aimed to determine ED RNs’ perceptions of SUDs and SCSs.Methods: A 27-question survey was sent to RNs currently working in EDs in Southwestern Ontario using an online Qualtrics® link. The research explored ED RNs’ perceptions of SCSs and SUDs.Results: Quantitative results indicated that ED RNs (n = 146) were empathetic toward drug use and SUDs, but felt neutral towars SCSs. They indicated positive impacts and potential concerns of SCS implementation. However, despite their apprehensions, most ED RNs reported that they would still refer their patients to such sites if one was available.Discussion: The findings from this study provided recent data on ED RNs’ perceptions of SUD and SCSs in small to mid-sized Canadian cities. It also identified services that SCSs and their EDs should offer from an ED RN perception.Conclusion: This multi-site research offers an opportunity to compare perceptions from other disciplines, share new knowledge, and improve patient care and safety. Recommendations include a harm reduction referral partnership between the ED and community partners. It is essential to practice reflexively, decrease the influence of stereotypes and stigma-based decisions and care, and encourage legislation that supports ethical policies and procedures that increase the use and access to SCSs.